2016
DOI: 10.1108/mi.2016.6687
|View full text |Cite
|
Sign up to set email alerts
|

Lady with erotic preference for diapers

Abstract: A patient in her 20s was referred to us for psychological assessment due to her depression and suicide attempts. She mentioned being anorgasmic except when diapered and emphasized her erotic preference for diapers. Her childhood included maternal deprivation in an impecunious family headed by an irritable physically disabled father on social assistance. Given the maternal deprivation in childhood, her erotic fixation on diapers parallels the emotional attachment to diapers observed by Harlow in mother deprived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…In this latter cases, a qualitative analysis made by Zamboni [15] showed that ABDL simulated excrementary functions with food or water to feel excited due to the dirty diaper's contact with their genitals; other individuals can focus on diaper tissue and the tactile feel for diaper touch on the genitals [15]; whereas other individuals use ABDL behaviours as a part of a bondage discipline sadism and masochism (BDSM) sexual practice. In this case, sexual arousal concerns the submission and humiliation that are inside the sado-masochistic relationships [3,9,15]. For example, Zamboni and Madero [18] made an analysis of asexual individuals in the online ABDL community, confirming the hypothesis that ABDL, like BDSM, could represent a way to decrease anxiety and to sexually satisfy a partner.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In this latter cases, a qualitative analysis made by Zamboni [15] showed that ABDL simulated excrementary functions with food or water to feel excited due to the dirty diaper's contact with their genitals; other individuals can focus on diaper tissue and the tactile feel for diaper touch on the genitals [15]; whereas other individuals use ABDL behaviours as a part of a bondage discipline sadism and masochism (BDSM) sexual practice. In this case, sexual arousal concerns the submission and humiliation that are inside the sado-masochistic relationships [3,9,15]. For example, Zamboni and Madero [18] made an analysis of asexual individuals in the online ABDL community, confirming the hypothesis that ABDL, like BDSM, could represent a way to decrease anxiety and to sexually satisfy a partner.…”
Section: Introductionmentioning
confidence: 91%
“…The man required psychological counselling because of gender dysphoria but he did not perceive ABDL interests as a distressing factor. Cernowsky and Bureau [9] reported a case of a woman affected by depressive symptoms and ABDL interests who was asking for help only for the former symptoms, not for the latter. Banbury, Lusher, Lewis, and Turner [10] described a case of two adults who practiced ABDL and had a drug addiction, showing that in both cases, either the addiction and the ABDL practices could be considered an auto-medication practices carried out to face sexual abuses during childhood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations